Structural Analysis of the OC43 Coronavirus 2'-O-RNA Methyltransferase - Dostalik, Pavel; Krafcikova, Petra; Silhan, Jan; Kozic, Jan; Chalupska, Dominika; Chalupsky, Karel; Boura, Evzen (Journal of virology, 2021)
The OC43 coronavirus is a human pathogen that usually causes only the common cold. One of its key enzymes, similar to other coronaviruses, is the 2'-O-RNA methyltransferase (MTase), which is essential for viral RNA stability and expression. Here, we report the crystal structure of the 2'-O-RNA MTase in a complex with the pan-methyltransferase inhibitor sinefungin solved at 2.2-Å resolution. The structure reveals an overall fold consistent with the fold observed in other coronaviral MTases. The major differences are in the conformation of the C terminus of the nsp16 subunit and an additional helix in the N terminus of the nsp10 subunits. The structural analysis also revealed very high conservation of the S-adenosyl methionine (SAM) binding pocket, suggesting that the SAM pocket is a suitable spot for the design of antivirals effective against all human coronaviruses. IMPORTANCE Some coronaviruses are dangerous pathogens, while some cause only common colds. The reasons are not understood, although the spike proteins probably play an important role. However, to understand the coronaviral biology in sufficient detail, we need to compare the key enzymes from different coronaviruses. We solved the crystal structure of 2'-O-RNA methyltransferase of the OC43 coronavirus, a virus that usually causes mild colds. The structure revealed some differences in the overall fold but also revealed that the SAM binding site is conserved, suggesting that development of antivirals against multiple coronaviruses is feasible.
Keywords: Protein Conformation, alpha-Helical; OC43; krystalografie rentgenová; virové proteiny; konformace proteinů, alfa-helix; methyltransferase; Betacoronavirus; vazebná místa; methyltransferasy; Crystallography, X-Ray; coronavirus; crystal structure; Methyltransferases; Binding Sites; Viral Proteins